BIODEGRADABLE PLASTIC FROM CASSAVA STARCH: A LITERATURE ANALYSIS - Sonia Linda Wibowo; Eka Cahya Muliawati; Amalia Zamzabila Putri; Azizah Dwi Anggraini; Mochamad Hasan Febrianto; Rafif Baskara Putra; Qori'atul Amaliyah (JURNAL PENA SAINS, 2025)
Plastic is a synthetic polymer derived from petroleum and contains hazardous additives, such as heavy metals and chlorine. The use of cassava starch as the main ingredient in bioplastics, a natural polymer, can be an environmentally friendly and biodegradable solution. However, cassava starch has limitations, such as its hydrophilic nature, poor mechanical strength, and poor stability. To address these issues, plasticizers such as glycerol and sorbitol are used to improve tensile strength, flexibility, and moisture resistance. Meanwhile, the addition of fillers can increase tensile strength, thermal resistance, and reduce hydrophilic properties, thereby improving the stability of bioplastics. Therefore, this review of biodegradable plastic research focuses on the use of cassava starch with the addition of various fillers that can be degraded by various processing techniques. To analyze the quality of these plastics, various testing methods are carried out, including physical, mechanical, thermal, and biodegradability tests, as well as structural and morphological analysis. The results of this research provide innovations that can be developed by making biodegradable plastic from cassava starch by combining a mixture of cassava starch with the addition of PLLA and CMC fillers and acetic acid as well as the addition of a combination of glycerol and sorbitol plasticizers.